Mechanisms Underlying the Impact of Interleukin Family on Acute Kidney Injury: Pathogenesis, Progression, and Therapy - Yuwei Ji; Zhenkai Zhao; Yan Yang; Xiaochen Wang; Ruifeng Qiao; Xiang Yu; Xinyan Gong; Zhe Feng; Quan Hong (Research)
Acute kidney injury (AKI) is a clinical syndrome with high mortality, and its pathogenesis involves complex inflammatory regulatory mechanisms. As core components of the cytokine network, interleukins (ILs) exert pleiotropic effects in the development of AKI, participating in processes such as inflammation, fibrosis, tissue damage repair, and remote organ injury. Moreover, ILs influence the progression of AKI by mediating the crosstalk among renal resident cells, immune cells, and fibroblasts. Pro-inflammatory ILs primarily accelerate the progression of AKI by recruiting neutrophils and inducing renal cell apoptosis, whereas anti-inflammatory ILs alleviate AKI by inhibiting the release of inflammatory cytokines and enhancing regulatory T cell function. Dual-function ILs may either promote disease progression or facilitate tissue repair depending on their cellular origin or the specific pathological stage. In terms of therapeutic strategies, monoclonal antibodies targeting ILs and their receptors, as well as advancements in extracellular vesicle technology, have shown promising potential. Future research should focus on elucidating the specific signaling networks of ILs and their intercellular interactions in order to promote precision medicine approaches for AKI and to block the transition from AKI to chronic kidney disease (CKD).